Preparation of PAN/PVDF Nanofiber Mats Loaded with Coconut Shell Activated Carbon and Silicon dioxide for Lithium-Ion Battery Anodes - Almafie, Muhammad Rama; Dani, Rahma; Riyanto; Marlina, Leni; Jauhari, Jaidan; Sriyanti, Ida (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Utilizing carbon materials derived from natural biomass holds significant promise for battery applications, owing to their low cost, abundant availability, and environmentally sustainable characteristics. However, graphite anode materials do not meet the demands of efficient batteries. Coconut shell waste has the potential to be used as activated carbon in energy storage anodes. By adding silicon dioxide (SiO2) to maintain structural stability and electrochemical reaction kinetics, the advantages of CCS can be maximized. Polyacrylonitrile/polyvinylidene fluoride (PAN/PVDF) composite polymer was used as a matrix to embed CCS/SiO2 and synthesize nanofibers via electrospinning. The resulting nanofibers had diameters ranging from to 575–707 nm, with cross-linked, porous, and beadless characteristics. Mechanical properties were measured by single-fiber micro tensile tests. The young modulus, tensile strength, and toughness of each nanofiber were successfully maintained at 13.7 ± 0.4 MPa, 34.4 ± 0.1 MPa, and 982 ± 10 kJ/m3, respectively, because of the presence of a β-crystal growth layer that facilitated efficient stress transmission. The reduction-oxidation process response had a potential difference of less than 1.286 V in the first cycle, whereas for the third and fifth cycles, it was maintained below 3.416 V. The lithium-ion diffusion coefficient was below 4.73×1013 cm2/s. Using the anode directly, as in lithium-ion batteries, provided a high capacity of 382 mAh/g after 200 cycles. Good cycle stability, with over 98% retention of the initial capacitance after 200 charge/discharge cycles, underscores its potential for application in lithium-ion batteries.